2004
DOI: 10.1103/physrevb.69.214402
|View full text |Cite
|
Sign up to set email alerts
|

Nano-oxide-layer insertion and specular effects in spin valves: Experiment and theory

Abstract: We report a systematic study of NOL ͑nano-oxide-layer͒ insertion and specular effects on the giant magnetoresistance ͑GMR͒ of single, synthetic, and dual spin valves, using a semiclassical Boltzmann theory. It is confirmed that the GMR ratio is enhanced by NOL insertion inside the pinned layer or after the free layer. The enhancements are primarily due to the contribution of the majority carriers. The NOL insertions inside the inactive layers of spin valves such as the seed, under, and capping layers reduce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 65 publications
5
12
0
Order By: Relevance
“…Figure 7͑a͒ shows that the GMR increases as the NOL position approaches the Co/NiMn interface. This result compares well with the findings of Wang et al 19 on CoFe/Cu/CoFe spin valves and Suh and Ross 20 on NiFe/Cu/Co ͑pseudo͒ spin valves. Wang et al have also observed that the GMR vanishes when the NOL approaches the interface between the pinned FM layer and the Cu spacer layer.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Figure 7͑a͒ shows that the GMR increases as the NOL position approaches the Co/NiMn interface. This result compares well with the findings of Wang et al 19 on CoFe/Cu/CoFe spin valves and Suh and Ross 20 on NiFe/Cu/Co ͑pseudo͒ spin valves. Wang et al have also observed that the GMR vanishes when the NOL approaches the interface between the pinned FM layer and the Cu spacer layer.…”
Section: Resultssupporting
confidence: 94%
“…The increase in the GMR can be attributed to the specular electron scattering at the Co/NOL interface. The relative increase in 20 % and the absolute GMR values compare well with the results of Wang et al 19 obtained for IrMn/CoFe/Cu/CoFe spin valves. Wang et al find a maximum increase in the GMR from 6% to about 9 % by inclusion of the NOL in the pinned CoFe layer.…”
Section: Resultssupporting
confidence: 90%
“…This allows both magnetizations either parallel (low resistance) or antiparallel (high resistance) to be obtained with an externally applied magnetic field. The nano-oxide layer NOL inserted either adjacent to the pinned layer or free layers [46][47][48] can highly enhance the majority spin orientated electrons specularly scatter at NOL [49,50] and thus a high dR/R.…”
Section: Discussionmentioning
confidence: 99%
“…The nano-oxide layers (NOLs) were widely employed in conventional pseudo-SVs (PSVs) to extend the mean free path of majority spin-polarized electrons through specular electron scattering at the NOL/pinned (free) layer interface and enhance GMR ratio [14][15][16][17][18][19][20]. To date, there is no report on NOL-based SVs or PSVs with full-Heusler alloy electrodes.…”
Section: Introductionmentioning
confidence: 99%